Reproductive consequences for Great Skuas specializing as seabird predators - Votier, S.C.; Bearhop, S.; Ratcliff, N.; Furness, R.W. (The Condor, 2004)
Most of the Great Skuas ( Stercorarius skua ) breeding at Hermaness, Shetland, exhibit dietary specialization: a small proportion feed almost exclusively upon seabird prey, a small proportion feed as generalists, and most feed on fishery discards. We investigated the foraging dynamics, reproductive performance, and survival of Great Skuas that specialized in depredating other seabirds compared with those feeding predominantly on fish. Around half of the specialist bird predators defended combined breeding and feeding territories that included a section of seabird colony; the remainder of the predatory skuas foraged away from breeding territories. Specialist bird predators retained their feeding habit and, if present, feeding territory, across years, Time budgets revealed that specialist bird predators spent less time foraging than skuas feeding predominantly on fish. Results of radio-telemetry indicated that bird-specialist skuas have smaller home ranges than other birds. In a comparison of reproductive performance, specialist bird predators consistently hatched earlier among years. They also showed larger clutch volumes and improved chick condition, but these were subject to annual variations. Hatching success and fledging success for specialist bird predators and specialist fish predators were similar. Specialist bird predators showed similar annual survival compared with fish-feeders over the same period. Specializing as a bird predator may be limited to the best birds in the population, but their poorer than predicted breeding success reveals the need for further study into the relationship between diet and reproductive success in this species.